Penentuan Harga Pokok Produksi Garam Pada Ud Apel Merah Rembang - Lis Widowati (Graha Akuntansi, 2023)
The purpose of this study is to determine the calculation of the cost of production of salt at UD. Red Apples Rembang and compare the calculation of the cost of production between companies using the full costing method. The type of research used is descriptive research using a qualitative approach. The data used in this study are primary data obtained directly from the company as well as company data in the form of information on production costs during August 2018. As for secondary data obtained from books, journals, the internet or other media that support this research. From the results of data analysis, the results of the study show that the calculation of the company's production price is lower than the calculation of the cost of production using the full costing method. The cost of production is calculated using the company method, which is IDR 2,268 per kg and IDR 2,276 according to the full costing method. This is because in the calculation of factory overhead costs the company does not take into account several costs into the cost of production such as the cost of maintenance and maintenance of production equipment, and the cost of depreciating equipment.